Science project ideas about rain - Gardner, Robert, 1929-; Katari, Jacob (Berkeley Heights, NJ : Enslow, 1997)
Uses experiments to illustrate the properties of rain as well as the reasons that water is such an important part of life.
Includes bibliographical references (p. 94) and index.
School Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Junior High School.
5.8.
5.8
Keywords: Clouds -- Experiments -- Juvenile literature; Rain and rainfall -- Experiments -- Juvenile literature; Clouds -- Experiments; Experiments; Rain and rainfall -- Experiments; Clouds; Meteorology -- Experiments; Rain; Science -- Experiments